EDUCATION AS A TOOL TO IMPROVE THE COMPETITIVENESS OF THE ECONOMY - Voronina, O.; Moskvina, A.; Yarmak, O. (Municipal economy of cities. Series: «Economy science», 2022)
The article considers the interaction of education and all spheres of public life. It is shown that education has lost its natural role and is used as a tool of society management. Ideological government is implementing the concept developed in favor of the powerful, using information flows in which education is of paramount importance. Organized in this way, the education system is an important element of manipulation technologies, so that society is programmed to certain actions to maintain the established order. The article reveals that the degree of influence on human consciousness depends on the level of human education. The degradation of education covers the whole world. This requires rethinking the meaning and essence of education, returning it to its former natural functions. The article shows that the formation of an adequate education system is possible only if it is reformed and attracts investment in this strategically important sector, which can raise the economy to a much higher level of development and competitiveness. Only the sphere of the mind can indicate the way out of this situation. The article proposes ways of reforming education by existing forces and knowledge, counteraction at the level of ideas and meanings. In the formation of a new education system it is proposed: to increase the availability of quality education; reorientation to human training in rapidly changing conditions with intensive development of social and economic processes; preserving the fundamentals of education in becoming a mature, socially responsible citizen; introduction of continuing education with competencies, methodology and culture of independent cognition, self-development, the desire to increase individual potential through the acquisition of new knowledge and skills; ensuring the advanced nature of the development of education, its focus on the demands and values of future civilization, which will meet its true essential functions. This will help society to resist manipulation, create positive useful ideas, knowledge, innovations and inventions, strengthen the sovereignty of countries, their positions on the world stage and increase the competitiveness of their economies.